If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(5 + 2x) + 5 = c 6x + (5 * -1 + 2x * -1) + 5 = c 6x + (-5 + -2x) + 5 = c Reorder the terms: -5 + 5 + 6x + -2x = c Combine like terms: -5 + 5 = 0 0 + 6x + -2x = c 6x + -2x = c Combine like terms: 6x + -2x = 4x 4x = c Solving 4x = c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 0.25c Simplifying x = 0.25c
| -1x+4y=-9 | | 3.5=1.5/x | | 5y-7y=2y+8 | | x=175000+.1x | | x^2+10n-39=0 | | 20=2g+3g | | (6x-1)(4x+6)= | | -3x-1y=-13 | | e^4=16 | | e^4=6 | | Los(x+25)=3 | | 21x+115=-3x^3+12x^2+17 | | (2x-5)=-3 | | 9/16-33/4 | | 16r+15=-r^2 | | 9y-30=60 | | 3k^2-27k+10=0 | | 5n+119=14n-7 | | 12*x+48=51*x-117 | | X=16a+1 | | 77077= | | 2y=y+11 | | (2x-4)/x=2 | | Ln(x^2-1)=1 | | X+.09x=11 | | 3(2-3x)-4=-(4x-5)+2 | | 62x+110=668 | | 62x+110=168 | | 5/6/1/7 | | Y-3=0(x-4) | | 2x+3=4(2+1) | | content://media/external/file/31459 |